Moderated Online Social Therapy for Young People With Active Suicidal Ideation: Qualitative Study - Bailey, Eleanor; Robinson, Jo; Alvarez-Jimenez, Mario; Nedeljkovic, Maja; Valentine, Lee; Bendall, Sarah; D'Alfonso, Simon; Gilbertson, Tamsyn; McKechnie, Ben; Rice, Simon (JMIR Publications, 2021)
BackgroundWeb-based interventions are a promising approach to support youth at risk of suicide, and those incorporating peer-to-peer social networking may have the added potential to target interpersonal states of perceived burdensomeness and thwarted belongingness. Owing to feasibility and safety concerns, including fear of contagion, this had not been tested until recently. In 2018, we conducted a pilot evaluation to test the feasibility, safety, and acceptability of a Moderated Online Social Therapy intervention, called Affinity, with a sample of young people with active suicidal ideation. ObjectiveThe aim of this study is to report qualitative data collected from study participants regarding their experience of the web-based social network and the consequent safety features. MethodsAffinity is a closed website incorporating 3 key components: therapeutic content delivered via comics, peer-to-peer social networking, and moderation by peers and clinicians. Semistructured interviews were conducted with 17 young people who participated in the pilot study after 8 weeks of exposure to the intervention. Interview data from 2 young people who did not use Affinity were excluded from the analysis. The interviews were analyzed using thematic analysis, with the frequency of responses characterized using the consensual qualitative research method. The results are reported in accordance with the Consolidated Criteria for Reporting Qualitative Research checklist. ResultsA total of 4 overarching themes were identified: a safe and supportive environment, the importance of mutual experiences, difficulty engaging and connecting, and the pros and cons of banning discussions about suicide. Interestingly, although Affinity was perceived to be safe and free of judgment, concerns about negative evaluation and triggering others were significant barriers to posting on the social network. Participants generally supported the banning of conversations about suicide, although for some this was perceived to reinforce stigma or was associated with frustration and distress. ConclusionsThe results not only support the safety and potential therapeutic benefit of the social networking aspect of Affinity but also highlight several implementation challenges. There is a need to carefully balance the need for stringent safety and design features while ensuring that the potential for therapeutic benefit is maximized.